Estrategias para mejorar la Comprensión Lectora, en los estudiantes de sexto grado de educación general básica paralelo A, de la escuela de educación básica Dr. Manuel Benjamín Carrión Mora, cantón y provincia de Loja, periodo académico 2014-2015 - Tigasi Cuenca, Diana Cristina (2016)
This thesis entitled strategies to improve reading comprehension IN SIXTH GRADE STUDENTS BASIC GENERAL EDUCATION PARALLEL TO, SCHOOL OF BASIC EDUCATION DR. BENJAMIN MANUEL MORA CARRIÓN, CANTON AND LOJA PROVINCE, ACADEMIC 2014-2015. Its general objective is to determine the application of appropriate strategies to improve reading comprehension, students in sixth grade of General Basic Education Parallel A, School of Basic Education Dr. Benjamin Carrion Manuel Mora. The research design was cross-sectional and quasi-experimental and methodology I used were comprehensive, analytical, synthetic and scientific instruments applied were the surveys thirty-one students and a survey of teaching, obtaining as results research that most students are located at level 1 reading, ie comprise only small and simple texts; plus most of them do not apply any strategy for reading comprehension and disclosed that the greatest difficulty with reading comprehension strategies is that not also apply previous knowledge shortages and poor vocabulary is given. It is concluded that the application of model strategies by the researcher using the workshop method directly benefited students and teachers, helping to reduce the difficulties presented by students in the development of reading comprehension, tested by Pearson's r. The implementation of strategies reading comprehension power and helps improve learning.